(untitled) (Fiep Bulletin - online, 2019)
Introduction: The promotion of physical activity in school is characterized by improvements in the quality of life forstudents. In this context, the physical education teacher’s has a fundamental role in school, and it is essential to act in thesecases. Training during the graduation course in physical education on how to act in emergency situations lead to act in differentsituations. Methodology: Bibliographic review by subject. Original and review articles were used between 2010-2018 obtainedfrom researches conducted in electronic databases and free-access scientific sites: (Scielo-Scientific Electronic Library Online,Periodicals Capes and PubMed), where the terms "Physical Education", "First Aid", "Injuries", "School", "Emergency", "Teacher",and "Knowledge" were used. Objective: To carry out a bibliographical review on the preparation of physical education teachers inthe school environment related to first aid. Conclusion: The school physical education teacher is not prepared to perform thenecessary first aid procedures. This unpreparedness results from the absence of continuing education on the subject aftergraduation that is pointed out as a means of keeping teachers up to date and prepared. Physical education teachers hasobligation to remain updating in first aid knowledge (e.g. training courses, congresses, lectures, among others). Furthermore, theinclusion of the content "Basic Notions of First Aid" in physical education classes is an interesting pedagogical tool.